1992
DOI: 10.1177/036354659202000409
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical evaluation of taping and bracing in reducing knee joint translation and rotation

Abstract: We used five randomly selected cadaver specimens to evaluate the Anderson Knee Stabler and the Lenox Hill Knee Brace, individually and in combination with an anterior cruciate ligament protective tape method. Reduction of total laxity, as well as a defined pathologic anterior-posterior translation and internal-external rotation, was tested after the anterior cruciate and medial collateral ligaments of the specimens had been sectioned. Displacements were produced pneumatically; loads were applied to the tibia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Athletic taping is used routinely in human physical therapy and sports medicine to stabilise, maintain, strengthen or act as a substitute for well-defined biological structures (Neiger 1990). Taping has clear biomechanical properties that include increasing joint stability, decreasing articular range of motion (Alt et al 1999), stabilising injured ligamentous structures (Anderson et al 1992) and reducing tendinous vibratory phenomena (Neiger 1990). Other described effects include an increase in local tissue temperature (Alt et al 1999), improved proprioceptive response (Beynnon and Renström 1991;Anderson et al 1992;Alt et al 1999), limitation of muscular action (Hopper et al 1999) and increase of the athlete's confidence (Neiger 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Athletic taping is used routinely in human physical therapy and sports medicine to stabilise, maintain, strengthen or act as a substitute for well-defined biological structures (Neiger 1990). Taping has clear biomechanical properties that include increasing joint stability, decreasing articular range of motion (Alt et al 1999), stabilising injured ligamentous structures (Anderson et al 1992) and reducing tendinous vibratory phenomena (Neiger 1990). Other described effects include an increase in local tissue temperature (Alt et al 1999), improved proprioceptive response (Beynnon and Renström 1991;Anderson et al 1992;Alt et al 1999), limitation of muscular action (Hopper et al 1999) and increase of the athlete's confidence (Neiger 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Wojtys et al 35 reported that the Lenox Hill brace (Lenox Hill Brace, Inc., Long Island City, New York) is effective in controlling internal tibial rotation under a 20 N·m torque load at 30° of knee flexion. In a later study, Anderson et al 3 compared the effects of a functional brace and athletic taping in five cadaveric limb specimens and found that knee bracing reduced anterior tibial translation by up to 20% and rotation by 16% at 125 N and 12 N·m of external loads, respectively.…”
mentioning
confidence: 99%
“…The efficacy of knee bracing is controversial. 3,13,14,26,37,43,44 Previous investigations of functional braces have been performed under various passive and muscle-activated loading conditions using arthrometers, 1,6,12,1618,37,42,45,47,49,51,55,56 roentgen stereophotogrammetry, 31 and direct measurement of ACL strain. 9,11,23 Most of these studies have been limited in that they have not incorporated the dominant effects of body weight and muscle loading.…”
mentioning
confidence: 99%